N-glycosylation Dictates Proper Processing of Organic Anion Transporting Polypeptide 1B1 - Yao, Juan (Public Library of Science, 2012)
Organic anion transporting polypeptides (OATPs) have been extensively recognized as key determinants of absorption, distribution, metabolism and excretion (ADME) of various drugs, xenobiotics and toxins. Putative N-glycosylation sites located in the extracellular loops 2 and 5 is considered a common feature of all OATPs and some members have been demonstrated to be glycosylated proteins. However, experimental evidence is still lacking on how such a post-translational modification affect the transport activity of OATPs and which of the putative glycosylation sites are utilized in these transporter proteins. In the present study, we substituted asparagine residues that are possibly involved in N-glycosylation with glutamine residues and identified three glycosylation sites (Asn134, Asn503 and Asn516) within the structure of OATP1B1, an OATP member that is mainly expressed in the human liver. Our results showed that Asn134 and Asn516 are used for glycosylation under normal conditions; however, when Asn134 was mutagenized, an additional asparagine at position 503 is involved in the glycosylation process. Simultaneously replacement of all three asparagines with glutamines led to significantly reduced protein level as well as loss of transport activity. Further studies revealed that glycosylation affected stability of the transporter protein and the unglycosylated mutant was retained within endoplasmic reticulum.